2010
DOI: 10.1016/j.ccr.2010.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Siah2-Dependent Concerted Activity of HIF and FoxA2 Regulates Formation of Neuroendocrine Phenotype and Neuroendocrine Prostate Tumors

Abstract: Summary Neuroendocrine (NE) phenotype, seen in >30% of prostate adenocarcinomas (PCa), and NE prostate tumors are implicated in aggressive prostate cancer. Formation of NE prostate tumors in the TRAMP mouse model was suppressed in mice lacking the ubiquitin ligase Siah2, which regulates HIF-1α availability. Cooperation between HIF-1α and FoxA2, a transcription factor expressed in NE tissue, promotes recruitment of p300 to transactivate select HIF-regulated genes, Hes6, Sox9 and Jmjd1a. These HIF-regulated gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
219
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(232 citation statements)
references
References 48 publications
13
219
0
Order By: Relevance
“…The genetic knockout of Siah proteins is valuable in establishing the significance of biochemical and cell biological studies. Finally, in both Siah1a and Siah2 null mice, tumor progression to an advanced stage was inhibited and metastasis was reduced [36] . These findings suggest that the inhibition of Siah expression is effective for attenuating tumor growth.…”
Section: Function Of Siah As a Tumor Sup-pressor Protein And Its Rolementioning
confidence: 99%
“…The genetic knockout of Siah proteins is valuable in establishing the significance of biochemical and cell biological studies. Finally, in both Siah1a and Siah2 null mice, tumor progression to an advanced stage was inhibited and metastasis was reduced [36] . These findings suggest that the inhibition of Siah expression is effective for attenuating tumor growth.…”
Section: Function Of Siah As a Tumor Sup-pressor Protein And Its Rolementioning
confidence: 99%
“…Siah1 and Siah2 are RING finger E3 ubiquitin ligases that regulate ubiquitination-mediated degradation of a range of signaling proteins, resulting in diverse biological effects such as resistance to apoptosis and effects on mitochondrial function. Qi et al 4 previously showed that knockout of the Siah2 gene in the TRAMP transgenic mouse model of PCa, a system that rapidly produces aggressive autochthonous prostate tumors that progress to metastasis, resulted in suppression of tumor formation. In a recent paper in Cancer Cell, 5 the same group has now gone on to uncover the mechanism of this surprising effect.…”
mentioning
confidence: 99%
“…Recently, the Src, STAT3 and AKT pathways, hyperactivated in NEPC, were shown to be stimulated by Reelin signaling in multiple myeloma corroborating the importance of Reelin signaling in NEPC [108,113]. Notably, Reelin induced upregulation of HIF1α in multiple myeloma, which has also been implicated in NEPC [108,114]. Upregulation of Reelin signaling components (MAP1B, MAPK8IP1, NDEL1) in NEPC tissue has been identified by RNA-seq [9].…”
Section: Discussionmentioning
confidence: 96%
“…Detection of AURKA amplification and overexpression in primary PCa specimens suggested its role as marker to identify patients that are more likely to develop NEPC [112]. Together, these finding indicate molecular parallels to the well-studied NE tumor models of neuroblastoma and small cell lung cancer and announce a crucial step towards a better understanding of the molecular pathogenesis of NEPC promoting the development of therapeutic strategies and identification of potential biomarkers [112][113][114][115].…”
Section: Neuroendocrine Prostate Cancermentioning
confidence: 88%
See 1 more Smart Citation